Policy Generosity, Employer Heterogeneity, and Women's Employment Opportunities: The Welfare State Paradox Reexamined. Issue 3 (June 2018) - Mun, Eunmi; Jung, Jiwook
Scholars of comparative family policy research have raised concerns about potential negative outcomes of generous family policies, an issue known as the "welfare state paradox." They suspect that such policies will make employers reluctant to hire or promote women into high-authority jobs, because women are more likely than men to use those policies and take time off. Few studies, however, have directly tested this employer-side mechanism. In this article, we argue that due to employer heterogeneity, as well as different modes of policy intervention such as mandate-based and incentive-based approaches, generous family policies may not always lead to employer discrimination. Adopting a quasi-experimental research design that classifies employers based on their differential receptivity to family policy changes, we compare their hiring and promotion of women before and after two major family policy reforms in Japan, one in 1992 and another in 2005. Our analysis using panel data of large Japanese firms finds little evidence of policy-induced discrimination against women. Instead, we find that employers who voluntarily provided generous leave benefits prior to government mandates or incentives actually hired and promoted more women after the legal changes, and employers who provided generous benefits in response to government incentives also increased opportunities for women.